Recent Development and Application of TiO2 Nanotubes Photocatalytic Activity for Degradation Synthetic Dyes A Review - Hasanah, Euis Uswatun; Kustiningsih, Indar; Slamet, Slamet; Baig, Maughal Ahmed Ali (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2021)
Synthetic dyes waste from textile industries, produce of the problematic pollutants in wastewater. TiO2 based photocatalysis are materials that exhibit excellent absorption behavior for organic compounds in wastewater due it properties including nontoxicity, high photocatalysis degradation ability, and chemical stabilities. However, several challenges exist regarding TiO2 nanotubes pure applications for dyes degradation such as poor affinity, high band gap energy, and difficulty of recovery and easy to recombination so it would decrease effectiveness of the photocatalysis process. Therefore, more design and optimization testing need to be conducted on the treatment conditions in order to reach higher removal efficiencies with lower costs. The modified physical properties by adding metal dopant, nonmetal, and sensitizer significantly enhanced photocatalysis activity. These parameters, which affect photocatalysis activity on degrade dyes waste pollutants, are discussed in the current review. As a result, the photocatalysis becomes more expected, and encourages to further research development.Keywords:TiO2, nanotubes, degradation, synthetic, dyes